Pengaruh Variasi Daya Microwave Pada Pengeringan Cabai Merah Terhadap Karakteristik Mutu Cabai Merah - Irwansyah Irwansyah; Syahirman Hakim; Amri Amri; Aidil Amar; Rustam Efendi (Politeknik Negeri Ketapang, 2025)
The research to determine a effect of microwave power on the quality of red chilies with variations in microwave power during drying. The research parameters are Moisture content, rehydration ratio and specific energy consumption (SEC), changes in color, texture and aroma. The data analysis by analysis of Variance (ANOVA). The input level of microwave power has an effect drying red chilies, which is able reduce moisture water content ranging from 9-12% bb with and time 140-180 minutes. Rehydration ratio ranges from 1.42-1.82 for dried red chilies due to good microwave power treatment for chilies at 200 Watt power treatment. The amount of energy consumption for drying red chilies is smallest in the 300 Watt treatment, which is 466.91 kWhg-1. The characteristics of red chili from organoleptic test were obtained from most color researcher (4.49) in the 250 Watt treatment, the best aroma (4.61) in the 250 Watt treatment and the best texture (4.81) in the 200 Watt treatment, but overall acceptance was most preferred panelists in the 250 Watt power treatment with an acceptance level of (3.89). From this study, it was obtained that there was a variation in the influence of microwave power variations on the quality of red.